American Shale Energy and the Global Economy Business and Geopolitical Implications of the Fracking Revolution - Thomas, Andrew R. (SpringerBriefs in Business,, 2018)
This brief explores the business and global implications of the American shale energy, or natural gas, revolution. Specifically, it provides a rational, comprehensive look at the major business themes and management implications that surround the new abundance of natural gas in the United States and identifies some of the most significant geopolitical considerations globally. While acknowledging some of the controversies and hazards surrounding the extraction techniques, commonly known as "fracking", the author also looks at the hopes this technique poses and details how shale energy will impact supply chains for firms. The discovery of new sources of domestic natural gas in recent years - coupled with innovations that facilitated their extraction - has altered the global landscape. However, the vast majority of the information out there for business students, faculty, and practitioners about the natural gas revolution is focused on the impact of "longer and lower" energy prices; and, secondarily, opportunities within the domestic energy sector. Each of these is crucial for business people to understand, however, the natural gas revolution is about much more. Companies of all sizes, whether they see it or not, are having new opportunities open up for their products and services. Further, the globalization of shale energy will have far reaching influence beyond simply economic factors. Geopolitical considerations and the re-structuring of international relations around shale energy will impact supply chains in a myriad of ways. This book aims to examine these opportunities. Featuring case studies from contemporary companies, this book will be of interest to students, academics, researchers, professionals and policy makers who are seeking to understand the business and global implications of the shale energy revolution.